Graphene Arrays: Direct Top‐Down Fabrication of Large‐Area Graphene Arrays by an In Situ Etching Method (Adv. Mater. 28/2015). (July 2015) - Geng, Dechao; Wang, Huaping; Wan, Yu; Xu, Zhiping; Luo, Birong; Xu, Jie; Yu, Gui
<x xml:space="preserve">Abstract</x> A chemical vapor deposition process is demonstrated by G. Yu and co‐workers on page 4195 to directly fabricate large‐area graphene arrays with full control over the size and orientation. Precise micro‐ and nanocutting of graphene film and single crystals are realized by introduction of hydrogen gas for in situ etching. This direct top‐down approach can enable atomically precise construction of integrated devices from single graphene sheets.